Evaluation of common bean genotypes for drought tolerance - Ribeiro, Tamires; Silva, Daiana Alves da; Fatima Esteves, Jose Antonio de; Giaretta Azevedo, Cleber Vinicius [UNESP]; Ribeiro Goncalves, Joao Guilherme; Morais Carbonell, Sergio Augusto; Chiorato, Alisson Fernando (Inst Agronomico, 2019)
The aim of this study was to evaluate twelve genotypes of common bean for intermittent drought stress and for root growth angle. The water deficit experiments were conducted in 2015 and 2016 in a randomized block experimental design with split plots and three replications. Two treatments were applied: an irrigated treatment and a water deficit treatment, in which irrigation was suspended in pre-flowering and remained suspended up to the time at which the matrix potential of the soil was measured to be near -199 kPa. At the maximum point of water deficit, physiological and morphological traits were evaluated, and at physiological maturity, the yield compounds and grain yield. To evaluate rootgrowth angle in 2016, a growth pouch system was used in a randomized block design, with five replications. Water deficit reduced genotype performance for all the traits except leaf temperature and first pod height. In relation to grain yield, the genotypes SEA 5 and Carioca Precoce performed better under water restriction conditions in both evaluations. The genotype Gen TS 4-7 performed better in the 2015 evaluation, and Gen TS 3-1 and Gen TS 3-3 in 2016. SEA 5, Gen TS 3-1, and Carioca Precoce had the highest harvest indexes in 2015; and Gen TS 3-1, Gen TS 3-2, Gen TS 3-3, Gen PS-4-3-1, IAPAR 81, Carioca Precoce, and SEA 5 in 2016. SEA 5 and Carioca Precoce had the best root growth angle and were considered sources of tolerance to water deficit.
Keywords: Phaseolus vulgaris; water deficit; grain yield; root growth angle